Unprecedented Synthesis of 2H,6H-1,5-Dithiocines Reinvestigated: A Structural Corrigendum Revealing Isothiazole-3(2H)-thiones - Banert, Klaus; Singh, Neeraj; Korb, Marcus; Lang, Heinrich (Synthesis, 2015)
The synthesis of postulated 2H,6H-1,5-dithiocines from isonitriles and acetylenedicarboxylates or dibenzoylacetylene in the presence of elemental sulfur was repeated. The products do not possess the structure of eight-membered sulfur heterocycles, but isothiazole-3(2H)-thiones were formed instead. This structural corrigendum was confirmed not only by a critical consideration of the 13C NMR spectroscopic data and by the correction of the MS spectra and the values of the elemental analyses but also by X-ray crystallographic structure determination. Several reaction mechanisms are discussed to explain the generation of the observed isothiazole-3(2H)-thiones.
Keywords: alkynes; heterocycles; multicomponent reaction; nucleophilic addition; ring closure; spectroscopy; structure analysis; sulfur